Memaksimalisasi Keuntungan Pada Outlet Nutime di Rantauprapat Dengan Menggunakan Metode Simpleks - Nst, Mayang Alvi Perdana; Mariyuandra, Alfanny; Pramudita, Dewi; Sinta, Evi Yulia; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
The aim of the research is to maximize the Nutime Outlet in Rantauprapat using the simplex method. Meanwhile, this research method is a quantitative research method, with a sample of Nutame Rantauprapat outlets. The sampling technique is a purposive sampling technique, the research instrument uses primary data types and sources. Primary data is collected directly through sources by conducting interviews, observations, submitting questionnaires, and so on. Data management and analysis uses the simplex method in PL manually. Based on the results of the analysis using the PL model using the simplex method, the maximum profit that can be obtained by Nutime Outlet traders is IDR 1,000,000.00- per Nutime drink production every dayNutime is one of Indonesia’s favorite drinks which is made from various flavours that have been determined before making the Nutime drink. Nutime was created by someone who aims to quench thirts when the weather is very hot. By creating a drink like Nutime, it makes it easier for residents or the public to get refreshing drinks. Nutime drinks are also made with various flovors available, such as the flavors that are popular among today’s young pople, namely read velvet, Chocolate, Moca, Taro and Mango. This Nutime drink is also served chilled to make it taste fresher. Therefore, we here are very interesed in conducting reasearch on drinks like Nutime to find out what ingredients are used to make the Nutime drink. This we conducted research using the simplex method.